Penerapan Metode Poster Comment pada Mata Pelajaran PAI di SDN 12 Limo Suku Sungai Pua - Andre Saputra; Desti Sartini (YASIN, 2026)
The visual media-based poster comment method provides students with opportunities to observe, discuss, express opinions, and connect learning materials with everyday life. However, studies describing the implementation process of this method and its supporting and inhibiting factors in Islamic Religious Education (PAI) at elementary schools remain limited. This study aimed to describe the implementation of the poster comment method in Grade V PAI instruction and to identify the factors supporting and inhibiting its implementation at SDN 12 Limo Suku Sungai Pua. This study employed a qualitative approach with a descriptive design. The informants comprised one Grade V PAI teacher as the primary data source and five Grade V students who were purposively selected. Data were collected through observation, structured interviews, and documentation and subsequently analyzed through data condensation, data presentation, verification, and conclusion drawing. The results showed that the poster comment method was implemented through four stages: selecting a poster appropriate to the learning material, observing and reflecting on the poster, conducting group discussions and providing comments, and formulating solutions or recommendations. The implementation of this method was supported by the availability of facilities, the attractiveness of the posters, student enthusiasm, group cooperation, a conducive classroom environment, and teacher guidance. Meanwhile, the inhibiting factors included limited time, differences in students’ abilities, lack of focus, and low self-confidence among some students. These findings emphasize that implementing the poster comment method requires relevant media, effective classroom management, and teacher guidance to ensure an optimal learning process. This study contributes to the development of active and contextual PAI instruction and provides practical guidance for teachers in designing and implementing visual media-based learning.